A re-examination of the role of religion in education (2013)
Religion has played major roles in other facets of human endeavours, be it political, economic, medical or educational. Right from the Middle Ages when the church reached its zenith of expansion, the field of education was positively enhanced with the establishment of about eighty universities in Western Europe. Interestingly, records showed that these universities were theologically oriented because they metamorphosed from schools attached to churches, Furthermore, the missionaries who propagated Christianity took along with the Gospel a certain kind of Education in order to enlighten their converts and train them in institutions they established. However, in recent years, some government’s policies have undermined the place of religion in education most especially in Nigeria. Religious subjects have been de-emphasized while science related courses are promoted in order to boost technological advancement. Secondly, individuals, corporate organizations and some educational institutions seem to have the notion that religion today has little or no relevance in education. No wonder the population of students into the Department of Religious Studies in few universities that offer them is low when compared with other departments in the Faculty. Furthermore, it is saddened to note that most of the private universities especially the mission-established ones do not give the study of religion the priority it deserves. This paper, therefore, seeks to investigate the reasons adduced the stakeholders on the neglect of religious education in academic circles with a view to determining the relevance of religion in the contemporary world.